Synthesis and characterization of Si nanoparticles wrapped by V2O5 nanosheets as a composite anode material for lithium-ion batteries. (10th August 2018) - Carbonari, G.; Maroni, F.; Birrozzi, A.; Tossici, R.; Croce, F.; Nobili, F.
Abstract: The preparation and the structural, morphological and electrochemical characterization of a Silicon/V2 O5 nanosheets composite (Si@V2 O5 ), as an active anode material for Li-ion batteries, are here reported. The nanocomposite material, aimed at mitigating the morphological instability issues commonly plaguing Si-based anodes, is prepared by a H2 O2 -based low-impact synthesis, while the electrode processing involves the use of Polyacrylic Acid (PAA) binder. The electrolyte formulation is optimized as well, by employing Vinylene Carbonate (VC) additive, in order to maximize cycling stability and performance. Preliminary results report specific capacities of 932 mAhg −1 and 759 mAhg −1 after 50 cycles at 500 mA g −1 and 1000 mA g −1, respectively. The Si@V2 O5 electrode also shows remarkable rate capability performance. Highlights: A Si/V2 O5 nanosheets composite anode delivering high reversible capacity is prepared. The use of vinylene carbonate additive to electrolyte enhances anode performance. Outstanding rate capability is delivered up to a current of 4 A g −1 . The combined use of V2 O5 nanosheets and VC stabilizes electrode/electrolyte interface.